2016
DOI: 10.1007/s13197-016-2465-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing quality characteristics of salami sausages formulated with whole buckwheat flour during storage

Abstract: This study was performed to investigate the quality characteristics of salami sausages added with different levels of whole buckwheat flour (BWF) during storage. Samples included the control (Con), addition of 1% BWF (T1), 3% BWF (T2), and 5% BWF (T3). Water activity (a) and pH decreased with increased level of BWF. Salami sausage samples containing 5% BWF demonstrated significantly lower 2-thiobarbituric acid (TBA) values than the control. Changes in TBA values between day 0 and 21 for T2 and T3 were less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…They attributed the reason for the increase in TBARS values to the oxygen permeability of the packaging material. Similarly, Park et al (2017) ascertained increases in TBARS values of salami sausages formulated with whole buckwheat flour until day 7 of storage while Alvarez et al (2011) found increases in TBARS values of frankfurters produced using rice bran until the 21st day of storage. Riazi et al (2016) established increases in TBARS values of meat emulsion systems produced using grape pomace.…”
Section: Resultsmentioning
confidence: 96%
“…They attributed the reason for the increase in TBARS values to the oxygen permeability of the packaging material. Similarly, Park et al (2017) ascertained increases in TBARS values of salami sausages formulated with whole buckwheat flour until day 7 of storage while Alvarez et al (2011) found increases in TBARS values of frankfurters produced using rice bran until the 21st day of storage. Riazi et al (2016) established increases in TBARS values of meat emulsion systems produced using grape pomace.…”
Section: Resultsmentioning
confidence: 96%
“…After 3 days of processing, the pH value was near 4.6 for all treatments, indicating that micro-organisms present in the fermenting starter culture produced lactic acid from the sugars present in the formulation, reducing the pH. Othes authors also reported a significant reduction of pH from day 0 to day 3 in the production of fermented sausage [11,12].…”
Section: Fig 1 Evolution Of Water Actitvy (A) Ph (B) and Weight Lomentioning
confidence: 88%
“…However, this task involves substantial knowledge in meat science and technological areas as well as sensory and regulatory aspects [55]. In this context, Park et al [59] investigated the quality characteristics of salami sausages added with different levels (1%, 3%, and 5%) of whole buckwheat flour (BWF; rich in dietary fiber, essential minerals and vitamins B1, C, and E) during storage. The addition of BWF to salami decreased a w after 21 days of storage.…”
Section: Adding Functional Ingredients Into Meat Products 221 Prebioticsmentioning
confidence: 99%